2004
DOI: 10.1007/s00247-004-1237-1
|View full text |Cite
|
Sign up to set email alerts
|

Definitive neuroradiological diagnostic features of tuberculous meningitis in children

Abstract: The presence of high density within the basal cisterns on non-contrast CT scans is a very specific sign for TBM in children. This will enhance diagnostic confidence, allow early institution of therapy and could reduce expenditure on contrast medium, scan time and radiation exposure. With the use of threshold techniques we believe that the pre-contrast hyperdensity may be detectable by a computer program that will facilitate diagnosis, and may also be modified to detect abnormal enhancement. Basal enhancement i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
51
0
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(58 citation statements)
references
References 46 publications
3
51
0
3
Order By: Relevance
“…In this report, brain CTs were highly suggestive of TBM (basal enhancement, hydrocephalus or tuberculoma) in 40% of the cases, similar results to those obtained by Andronikou et al (2004) who reported 41% sensitivity and 100% specificity for brain CTs in the detection of childhood TBM [21]. Another study, of Kumar et al, reported 89% sensitivity and 100% specificity for CT findings in the diagnosis of TBM [16].…”
Section: Discussionsupporting
confidence: 85%
“…In this report, brain CTs were highly suggestive of TBM (basal enhancement, hydrocephalus or tuberculoma) in 40% of the cases, similar results to those obtained by Andronikou et al (2004) who reported 41% sensitivity and 100% specificity for brain CTs in the detection of childhood TBM [21]. Another study, of Kumar et al, reported 89% sensitivity and 100% specificity for CT findings in the diagnosis of TBM [16].…”
Section: Discussionsupporting
confidence: 85%
“…Hydrocephalus per se is an unspecific lesion observed in bacterial meningitis, but the study of its features is related to a severe clinical picture [8] and its incidence increases with the duration of illness. Both of our fatal cases had severe hydrocephalus and were in an advanced stage of clinical presentation.…”
Section: Resultsmentioning
confidence: 99%
“…Modern imaging is a cornerstone of early CNS-TB diagnosis and may help to prevent unnecessary morbidity and mortality. Imaging techniques have recently been revealed as important diagnostic tools as they can demonstrate various conditions, such as intracranial tuberculomas, edema, ventricular dilatation and basal cistern enhancement [8,9] . Contrast-enhanced MR imaging is generally the preferred procedure to detect and assess CNS tuberculosis [10] .…”
Section: Introductionmentioning
confidence: 99%
“…CNS tuberculosis is the most lethal form of tuberculosis and its mortality is around 100% in untreated cases (1,9,10). TB meningitis usually occurs after primary infection in children; however, in adults it is reactivation of old tuberculous foci (2).…”
Section: Discussionmentioning
confidence: 99%
“…Tuberculosis is the most important worldwide health problem, and meningitis is its gravest form with high mortality and morbidity (1). Meningitis occurs in 1% of tuberculosis cases and its fatality rate is high, 15% to 40%, even with effective treatment.…”
Section: Introductionmentioning
confidence: 99%